CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

In fig., If PQ BC and PR CD. Prove that ARAD= AQAB. [4 MARKS]


Solution

Concept : 1 Mark
Application : 1 Mark
Proof : 2 Marks

In ΔABC, we have

PQCB                       [Given]

Therefore, by basic proportionality theorem, we have

AQQB = APPC

AQAB=APAC........(1)              

In ΔACD, we have

PRCD                     [Given]

Therefore, by basic proportionality theorem, we have

APPC = ARRD

APAC = ARAD........(2)                

From (1) and (2), we obtain that

AQAB = ARAD

or ARAD = AQAB

flag
 Suggest corrections
thumbs-up
 
0 Upvotes


Similar questions
View More


People also searched for
View More



footer-image